Moyamoya Disease: Results of Surgery - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
An angiographic study of the effects of encephalo-duro-arterio-synangiosis (EDAS) in 27 children with moyamoya disease is reported from the Departments of Radiology and Neurosurgery, Tokyo Medical and Dental University, Tokyo, Japan.